Estimating a System of Recreation Demand Functions Using a Seemingly Unrelated Poisson Regression Approach - Ozuna, Teofilo; Gomez, Irma Adriana (The Review of Economics and Statistics, 1994)
Teofilo Ozuna, Jr., Irma Adriana Gomez, Estimating a System of Recreation Demand Functions Using a Seemingly Unrelated Poisson Regression Approach, The Review of Economics and Statistics, Vol. 76, No. 2 (May, 1994), pp. 356-360